Trachealess--a new transcription factor target for PKB/Akt. - Downward, J.; Leevers, S.J. (Developmental Cell, 2001)
Applying a combined genetic and biochemical approach has led to the identification of a new protein kinase B/Akt target, the transcription factor Trachealess.